Regional integration in Latin America, globalization and south-south trade - Di Filippo, Armando (ECLAC Port of SpainTT, 1998)
Sets out the historical background to the features of regional integration in Latin America between 1960 and 1990. Examines the concept of open regionalism. Focuses on the negotiating procedures and the type of undertakings involved in the free trade agreements that have been signed up to in the hemisphere. Looks at regional and inter-regional free trade agreements in the 1990s. Describes how negotiations are conducted and what type of agreements are contained in those subregional integration schemes of Latin America and the Caribbean that have the objective of setting up customs unions and common markets. Looks at globalization and south-south trade.